Retoriche repubblicane: Venezia, Genova e il problema dell’orazione in creatione ducis (XV-XVII secolo) - Giovanni Florio (Laboratoire Italien)
Although apparently well-established in both Venice and Genoa, the custom of celebrating the doge with congratulatory orations experienced a deep crisis around the 1620s. This occurrence reflects a more generalised crisis: in both cities, but at different rates, a loss of meaning affected the whole republican polity shaking its foundations. The questioning of the perfection attributed to the civic-aristocratic order was reflected, in Venice as in Genoa, in a resurgence of the patrician scepticism towards the doge, the pseudo-monarchic persona intended as the synthesis and body natural of the Republic. By the beginning of the seventeenth century the symbolic and constitutional charisma of the republican prince was being questioned, lost meaning, and was consequently re-semanticised. The present article analyses these aspects through the prism offered us by the Genoese and Venetian political and literary debates addressing the production of in creatione ducis orations.